2014
DOI: 10.1007/s10551-014-2500-5
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Bad News: How Procedural Unfairness Affects Messengers’ Distancing and Refusals

Abstract: Drawing from a social predicament and identity management framework, we argue that procedural unfairness on the part of decision makers places messengers in a dilemma where they attempt to protect their professional image or legitimacy by engaging in refusals (e.g., curbing explanations) and exhibiting distancing behaviors (e.g., minimizing contact with victims) when delivering bad news. Such behaviors however, violate key tenets of fair interpersonal treatment. The results of two experiments supported our hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Akintoye, McIntosh, and Fitzgerald (2000), Akintoye and Main (2007) and Jha and Iyer (2007) emphasise in their research that commitment is a key factor for the successful project delivery and some studies related to organisational justice suggest that distributive, procedural and interactional justice predict organizational commitment (Allen & Meyer, 1990;Jason A. Colquitt et al, 2001;Folger & Konovsky, 1989). The same is applicable for conflict management which is an antecedent to project performance (Chan et al, 2004) and it has been suggested in prior research that organisational justice can be useful in difficult conversation or in delivering bad news (Lavelle, Folger, & Manegold, 2016;Richter, König, Koppermann, & Schilling, 2016).…”
Section: H1mentioning
confidence: 98%
“…Akintoye, McIntosh, and Fitzgerald (2000), Akintoye and Main (2007) and Jha and Iyer (2007) emphasise in their research that commitment is a key factor for the successful project delivery and some studies related to organisational justice suggest that distributive, procedural and interactional justice predict organizational commitment (Allen & Meyer, 1990;Jason A. Colquitt et al, 2001;Folger & Konovsky, 1989). The same is applicable for conflict management which is an antecedent to project performance (Chan et al, 2004) and it has been suggested in prior research that organisational justice can be useful in difficult conversation or in delivering bad news (Lavelle, Folger, & Manegold, 2016;Richter, König, Koppermann, & Schilling, 2016).…”
Section: H1mentioning
confidence: 98%
“…Research has shown that messengers' concerns about giving bad news are manifold, and include feelings of guilt toward those suffering from bad news (Tesser & Rosen, 1972), fears of negative evaluations and self-presentation concerns of being associated with bad news (Bond & Anderson, 1987), and anticipation of negative reactions of the recipients (Rosen & Tesser, 1970). In line with these findings, giving bad news to an employee can create considerable stress in managers, whether it pertains to the communication of negative hiring decisions or to the delivery of layoff news (e.g., Folger & Skarlicki, 1998;Lavelle et al, 2014). In some cases, for instance if managers do not support the decisions they have to convey (e.g., conducting a layoff due to downsizing rather than performance deficits), doing harm to an employee may also contradict a manager's role expectation of being a "good" supervisor who aspires to promote and support his or her employees (Kets de Vries & Balazs, 1997).…”
Section: Introducing Organizational Bad News Training the Bad News De...mentioning
confidence: 96%
“…-(George Clooney alias Ryan Bingham in the motion picture Up in the Air by Dubiecki, Clifford, Reitman, & Reitman, 2009) Giving bad news to an employee is as much a regular task for managers as it is a difficult one (Bies, 2013). Managers have to communicate not only organizational downsizing and layoffs (Clair & Dufresne, 2004), but also negative performance feedback (Ilgen & Davis, 2000), pay cuts (Greenberg, 1990), negative hiring (Lavelle, Folger, & Manegold, 2014) or promotion decisions (Lemons & Jones, 2001), or disciplinary warnings (Cole & Latham, 1997). What all these conversations have in common is the stress they arouse in managers and employees alike: Employees feel threatened by bad news because it impairs their self-esteem and creates uncertainty about their future (e.g., Baumeister, Bratslavsky, Finkenauer, & Vohs, 2001), and managers feel uncomfortable with their responsibility for giving this news and thus doing harm to the employee (e.g., Molinsky & Margolis, 2005).…”
mentioning
confidence: 99%
“…We used the vignette technique to present two typical real‐life ethical–economic decision dilemma scenarios (see Kotzian et al, 2016; Lavelle et al, 2016; Oll et al, 2018 for applications). By describing a situation and asking for a decision intention, the technique comes as close as possible to actual decision making.…”
Section: Research Design and Measurementmentioning
confidence: 99%